The limitations related to the implementation of the triage policy and the identification of factors which can be used towards addressing them, in selected public, tertiary hospital - Bell, Nomtha (Department of Public Health and Family Medicine, 2014)
The problem identified in this study was the inconsistency in the implementation of the triage system in this institution. We therefore wish to develop an understanding towards issues contributing to the irregular use of the triage system and wish to better understand the reasons behind this inconsistency. Through the knowledge of barriers, we could then work towards the optimal use of this system. This would be beneficial towards the reduction of overcrowding as well as the reduction of waiting times for patients accessing the EA [Emergency Areas].